Microwave-assisted extraction applied to Merlot grapes with contrasting maturity levels: effects on phenolic chemistry and wine color - Casassa, Luis Federico; Sari, Santiago Eduardo; Bolcato, Esteban Augusto; Fanzone, Martín Leandro (MDPI, 2019)
Merlot grapes were harvested with three maturity levels (21.1, 23.1, and 25.1 Brix), and processed with or without the application of microwave-assisted extraction (MW). The detailed phenolic composition and color were followed during winemaking. The MW treatment did not affect the basic chemical composition of the wines. Upon crushing, MW caused a 211% improvement in anthocyanins in the wines of the first harvest and an 89% improvement in the wines of the third harvest. At bottling, MW favored the formation of pyranoanthocyanins and tannin-anthocyanin dimers. Tannin extraction was not affected by MW just after application of this process, but improvements of 30, 20, and 10% on MW-treated wines of the first, second, and third harvest, respectively, were recorded at pressing. The formation of polymeric pigments during aging generally increased along with harvest date and was only favored in MW-treated wines of the first and third harvest, with preferential formation of small polymeric pigments, in accordance with enhanced anthocyanin extraction in these wines. Initial improvements of wine color upon application of MW in the wines of the first, second, and third harvest were of 275, 300, and 175%, respectively. Although these differences subsided or disappeared for the wines of the second and third harvest during aging, the wines of the first harvest treated with MW retained 52% more color than Control wines at day 150 post-crushing. Results suggest the MW treatment was more efficient in extracting and retaining phenolics and color when applied to unripe fruit.